Using Thomas-Fermi Formula of Level Density Parameter to Find New Single Particle Level Density Formula - Hadeer K. Mohammed; Ali D. Salloum (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The level density is a parameter that has great importance in the theoretical nuclear calculation, and it is considered a key of many theoretical studies, therefore, the level density in pre-equilibrium reaction or what is the so-called accurate partial level density PLD has been studied. The partial  level density PLD  used  in pre-equilibrium reactions is dependent on the parameter called single particle level density which can be calculated by two methods either using the equidistant spacing model (ESM) or non-equidistant spacing model (non-ESM)  In this study, the parameter   is estimated by using the relation between the level density parameter  and  based on Ericson and Williams's formulas (  )  is substituted from the Thomas-Fermi formula and the new  was substituted one-component Ericson's formula, two-components  Ericson's formula, Williams's formula, spin formula, and surface formula.  The results show that the PLD estimated from one-component Ericson's formula gives the best agreement with the experimental data between 4 MeV to 5 MeV.